STUDI KARAKTERISTIK REAKTOR GASIFIKASI TYPE DOWNDRAFT SERBUK KAYU DENGAN VARIASI EQUIVALENSI RATIO - Suliono, Suliono; Sudarmanta, Bambang; Dionisius, Felix; Maolana, Imam (P3M Politeknik Negeri Indramayu, 2017)
The depletion of fossil fuel reserves and natural gas makes people rethink to find alternative energy substitutes. Biomass is an alternative energy that is still abundant and has not been fully utilized. Gasification is one of alternative in gas making that change from solid fuel (wood powder) to thermochemical flammable gas. The research used downdraft gasification with experimental wood powder. The implementation of research was done in workshop of Indramayu State of Polytechnic, using batch system, it means once the import of biomass in the furnace from the beginning until the biomass out by 5 kg of wood powder biomass. Equivalence Ratio (ER) performed 4 variations namely: 1.01; 1.13; 1.34; 1.52. The recorded data are: temperature inside reactor, gasification operation time, air intake, syngas content, and flame visualization. The results obtained from the gasification process showed if the Equivalence Ratio (ER) is higher so the heating value of syngas decrease. LHV at ER 1.52 of 3980,306 Kj / m3 and the synthetis gas content decreased as much as 21,7806 %